Arts Pedagogy in Non-Formal Learning at the Rossy Entertainment Studio - Farach Hasan Maulidah; Wiwin Purwinarti; Syamsul Rizal (EDUJAVARE: International Journal of Educational Research, 2026)
The role of Non-Formal Education in the development of art is increasingly important in the midst of the limitations of expression space in formal education which tends to be structured and curriculum-oriented. This study aims to analyze the practice of Art Pedagogy in the context of Non-Formal Education at Sanggar Rossy Entertainment. The approach used is qualitative with phenomenological design to explore the experiences of trainers, students, and managers in the art learning process. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using coding techniques and thematic analysis assisted by NVivo. The results show that art learning in the studio takes place through a practice-based approach (learning by doing) that emphasizes direct experience, social interaction, and reflection. The pedagogical strategies used include demonstration, imitation, exploration, repetitive exercises, and improvisation, which together support the development of students' skills and creativity. In addition, learning takes place in a flexible, participatory, and community-based environment, with evaluations emphasizing process through performance and experiential reflection. Theoretically, these findings reinforce the relevance of Experiential Learning and Constructivism in non-formal arts learning. The novelty of this research lies in the community-based model of art pedagogy that is contextual, embodied, and cyclical. This research contributes to the development of the study of art pedagogy as well as practical implications for the management of art learning in a non-formal environment.